2018
DOI: 10.1007/s00464-018-6069-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the application of a bundle of three measures (intraperitoneal lavage with antibiotic solution, fascial closure with Triclosan-coated sutures and Mupirocin ointment application on the skin staples) on the surgical site infection after elective laparoscopic colorectal cancer surgery

Abstract: The addition of intraperitoneal lavage with antibiotic solution, fascial closure with Triclosan-coated sutures and Mupirocin ointment application on the skin staples, to a standard bundle of SSI prevention, reduces the incisional and organ-space SSI and consequently the hospital stay, after elective laparoscopic colorectal cancer surgery (ClinicalTrials.gov Identifier: NCT03081962).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…The first site of infection, in terms of timing, is the superficial incision [2]. We must not underestimate this problem because it has a significant impact on morbidity, mortality, length of hospital stay and overall costs [3]. There are many ways to reduce the rate of SSIs both peri-and intra-operatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first site of infection, in terms of timing, is the superficial incision [2]. We must not underestimate this problem because it has a significant impact on morbidity, mortality, length of hospital stay and overall costs [3]. There are many ways to reduce the rate of SSIs both peri-and intra-operatively.…”
Section: Introductionmentioning
confidence: 99%
“…SSIs mostly occur in patients who underwent abdominal surgery; for this reason, the general surgeon deals with this important clinical problem on a daily basis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the heterogeneity there was significant reduction in the risk of SSIs by 46% (RR=0.54; 95% CI, 0.46-0.64; p<.00001, I 2 =73%) (Figure 2). 22 of the 25 studies had a statistically significant decrease in overall SSI rates following bundle implementation [16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Two studies showed no effect [21,40] and Anthony, et al 2011 [15] reported a statistically significant increase in SSI after bundle implementation.…”
Section: Wound Bundle and Their Effect On Surgical Site Infection Ratesmentioning
confidence: 99%
“…Most studies (n = 33) reported overall SSI incidence ( Table 1). Several studies did not report overall SSI incidence but did report superficial SSI incidence (n = 4), 14,[38][39][40] and/or organ-space SSI incidence (n = 3) 41,42,51 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…(2) normothermia maintenance in 32 studies (80%); (3) perioperative glucose control in 22 studies (55%); (4) appropriate hair removal in 20 studies (50%); (5) mechanical and oral bowel preparation in 18 studies (45%); (6) preoperative bathing with chlorhexidine in 16 studies (40%); (7) standardized postoperative dressing removal and wound care in 16 studies (40%); (8) wound closure protocol including glove with or without gown change and separate instrument tray in 15 studies (38%); (9) use of wound protectors in 11 studies (28%); (10) use of supplemental oxygen postoperatively in 7 studies (18%); (11) cutaneous antisepsis with a solution containing chlorhexidine gluconate and isopropyl alcohol in 6 studies (15%); (12) preoperative smoking cessation in 4 studies (10%); (13) wearing appropriate surgical attire, restricted to the operating room (OR) in 2 studies (5%). Other interventions included minimizing OR traffic, 19,20,22,46,51 peritoneal lavage with antibiotics, 14,43 wound irrigation with antibiotic solution 15,26 or with saline before closure, 16,23,29,31,40 postoperative daily chlorhexidine showers, 18,21,32 and daily wound cleaning with chlorhexidine. 32,46,51 Adherence to colorectal SSI prevention bundles Adherence to colorectal SSI prevention bundles was reported in 28 studies (70%).…”
Section: Composition Of Colorectal Infection Prevention Bundlesmentioning
confidence: 99%